2023
DOI: 10.1371/journal.pone.0284081
|View full text |Cite
|
Sign up to set email alerts
|

On the Quina side: A Neanderthal bone industry at Chez-Pinaud site, France

Abstract: Did Neanderthal produce a bone industry? The recent discovery of a large bone tool assemblage at the Neanderthal site of Chagyrskaya (Altai, Siberia, Russia) and the increasing discoveries of isolated finds of bone tools in various Mousterian sites across Eurasia stimulate the debate. Assuming that the isolate finds may be the tip of the iceberg and that the Siberian occurrence did not result from a local adaptation of easternmost Neanderthals, we looked for evidence of a similar industry in the Western side o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…On the other hand, the combination of different pits, scores, and active areas types (Mallye et al, 2012) suggests that there was a reuse of those retouchers that were most suited to the production of different lithic tools. In the literature, the presence of retouchers is associated either with the presence of tools with Quina-type retouch (Baumann et al, 2023;Mozota, 2012) or with discoid-type tools (Martellotta et al, 2020). Experimental work (Mallye et al, 2012) has…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the combination of different pits, scores, and active areas types (Mallye et al, 2012) suggests that there was a reuse of those retouchers that were most suited to the production of different lithic tools. In the literature, the presence of retouchers is associated either with the presence of tools with Quina-type retouch (Baumann et al, 2023;Mozota, 2012) or with discoid-type tools (Martellotta et al, 2020). Experimental work (Mallye et al, 2012) has…”
Section: Discussionmentioning
confidence: 99%
“…It is a very expeditious technological appliance usually discarded after use, and more frequently associated with the Middle Palaeolithic (Barandiarán, 1987;Baumann et al, 2023;Hutson et al, 2018;Mozota, 2012Mozota, , 2015Romandini et al, 2015;Vincent, 1993), although some have also been recorded in the African Middle Stone Age (MSA), and are a recurring object in a variety of epochs and contexts (e.g., Doyon et al, 2018;Mallye et al, 2012;Martellotta et al, 2021;Rosell et al, 2015;Tejero et al, 2016). Commonly shaft fragments of ungulates are used, but there are other instances including even the use of human remains (Verna & D'Errico, 2011).…”
mentioning
confidence: 99%
“…[48,[56][57][58][59][60]). As an example, the bone assemblage from the Quina Mousterian levels within the collapsed rock shelter at Chez-Pinaud (Charente-Maratime, France) provides a useful illustration of the characteristics of Mousterian knapping tools [61].…”
Section: Middle Palaeolithic In the European 'Core' Areamentioning
confidence: 99%
“…These visits were primarily focused on butchering hunted reindeer at the site. In addition to the 510 retouchers previously studied from earlier excavations, Baumann et al [61] undertook a comprehensive analysis of an additional 83 retouchers, primarily consisting of diaphyseal splinters, from a recent excavation of the Quina levels. Baumann observed that bone retouchers were made equally from medium-and large-sized ungulates, suggesting that Neanderthals at the site royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Middle Palaeolithic In the European 'Core' Areamentioning
confidence: 99%
See 1 more Smart Citation